1936
DOI: 10.1084/jem.63.4.523
|View full text |Cite
|
Sign up to set email alerts
|

Concerning the Relation of Environmental Temperature to Resistance to Thyroid and Thyroxine, and the Creatine Content of the Heart and Other Tissues in Experimental Hyperthyroidism

Abstract: In 1919 Stoland and Kinney (1) published a brief statement concerning the relation of external temperature to the toxicity of administered thyroid. They found that rats kept at 32°C. and receiving 0.2 gin. of desiccated thyroid daily, lived an average of 7.3 days; others at 25°C. lived an average of 22 days, while a third group kept at 180C. lived more than 32 days. A survey of the literature reveals no other reports specifically concerned with this question, although the more general problem of the relation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1937
1937
1975
1975

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Changes in the ability of the muscles to store or liberate creatine or phosphocreatine Analyses of muscles have shown that the concentration of creatine is decreased in thyrotoxicosis (4,26,27), in progressive muscular dystrophy (39,44) and in denervation atrophy (41 ). Wang (4) demonstrated increased creatine and phosphocreatine in the muscle of thyroidectomized rabbits, and Williamson and Gulick (42) The observations which we have recorded suggest that it has little, if any, influence.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Changes in the ability of the muscles to store or liberate creatine or phosphocreatine Analyses of muscles have shown that the concentration of creatine is decreased in thyrotoxicosis (4,26,27), in progressive muscular dystrophy (39,44) and in denervation atrophy (41 ). Wang (4) demonstrated increased creatine and phosphocreatine in the muscle of thyroidectomized rabbits, and Williamson and Gulick (42) The observations which we have recorded suggest that it has little, if any, influence.…”
mentioning
confidence: 71%
“…Muscle creatine and phosphocreatine in hyperthyroidism and hypothyroidism In thyrotoxic rats a significant decrease of the creatine content of the striated muscle (26) and a decrease of both phosphocreatine and creatine in heart muscle (27) has been demonstrated. Wang (4), using improved methods, studied both creatine and phosphocreatine in rabbits.…”
mentioning
confidence: 99%
“…There is experimental evidence that the maintenance of body temperature is thyroid‐dependent at low environmental temperatures (Bodansky et al 1936; Lancet 1956) and that there is increased activity of the thyroid gland in euthyroid animals exposed to cold (Bigelow and Sidlofsky 1961). Hypothyroid animals are less able to withstand exposure to cold (Leblond and Eartly 1952) and their body temperature falls more rapidly (Laties and Weiss 1959).…”
Section: Treatmentmentioning
confidence: 99%